Pyridoxine-Dependent Epilepsy and Pipecolic Acid - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
Two neonates with pyridoxine-dependent epilepsy and significant elevation of pipecolic acid in plasma and CSF are reported from the University Hospital Vienna, Austria.